Modern MRI tools for the characterization of acute demyelinating lesions: value of chemical shift and diffusion-weighted imaging. - Küker, W; Ruff, J; Gaertner, S; Mehnert, F; Mader, I; Nägele, T (2004)
Acute demyelinating lesions occur in various inflammatory disorders of the CNS. Apart from multiple sclerosis, most cases can be attributed to an overshooting immunological response to infectious agents called acute disseminated encephalomyelitis (ADEM). ADEM, which is mostly characterized by a monophasic course, has a multiphasic variant (MDEM). The early application of corticosteroids has been shown to be beneficial for the outcome; thus, an early diagnosis is highly desirable. Furthermore, the differential diagnosis ruling out neoplastic disorders may be difficult using conventional MRI alone. The potential diagnostic value of advanced MR techniques such as chemical shift imaging (CSI) and diffusion-weighted imaging (DWI) was investigated in a patient with MDEM, who had a new lesion in continuity with the initial disease manifestation. CSI was performed at 1.5 T with a long echo time of 135 ms for the evaluation of N-acetyl-aspartate (NAA) and choline (Cho) and with short TE of 30 ms for macromolecules (mm) and myo-Inositol (mI). DWI was performed using a single-shot isotropic EPI sequence. Whereas acute and chronic areas of demyelination were neither distinguishable on T2- nor on contrast-enhanced T1-weighted images, CSI and DWI revealed different metabolite concentrations and diffusion characteristics within the composite lesion, clearly separating acute from chronic areas of demyelination. In conclusion, the addition of CSI and DWI may add to the diagnostic power of MRI in the setting of demyelinating disorders by identifying areas of acute and chronic demyelination, even in the absence of contrast enhancement.